DETECTION OF THE SEASONAL VARIATIONS OF POTATO SALES IN WHOLESALE MARKETS OF BAGHDAD PROVINCE DURING THE PERIOD (2010-2015) AND FORECASTING BY USING SEASONAL TIME SERIES MODELS(SARIMA) - & Al-Ani, Alhiyali (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2018)
This research was aimed to detect the seasonal phenomenon of the monthly sales of potato crop in Baghdad for the period (January 2010 - December 2015), using the krusskle - Wallis method. The research also aimed to determine the shape of the time series of the monthly sales of the potato crop whether to follow additive or multiplicative model. The problem of the research is presence of the seasonal phenomenon in the monthly sales of the potato crop, which will be reflected in one way or another on the short-term planning process. According to the results obtained, the monthly sales of the potato crop were predicted at 60 observations for the period January 2016 - December 2020, where the results were consistent with those in the original time series. We conclude from the results obtained that the monthly sale of the potato crop contains seasonal variations and confirms the nature of the pattern that the potato crop has been affected by the season to a large extent. This research was concluded that there was an increase in sales of potato crop during specific months of the year. This is confirmed by the results of the research, which will be reflected in one way or another on the low prices in the months of high sales according to the law of supply and demand. The research included recommendations such as preventing import at peak time (peak season of production) and the need to work on the development of laws and legislation to protect local agricultural products. The research also recommended the imposition of taxes and customs duties on imported agricultural products and not to allow entry into Iraq during the peak season of production.